Structural brain MRI studies in autism spectrum disorder - J. M. Petrović; I. Binic; A. Stojanovic; M. Zdravkovic; F. Petrovic (European Psychiatry, 2023)
Introduction Autism spectrum disorder (ASD) refers to a group of conditions characterized by quantitative differences in the morphology of the cortex and subcortex. Analyzing brain morphology qualitatively provides complementary information about possible underlying neurobiology. Studies of neuroradiological findings in ASD have produced mixed results in a large and independent sample. Objectives A small cerebellum associated with pons hypoplasia, or a posterior fossa cyst, may indicate causal developmental mechanisms. Therefore, neuroradiological findings could help elucidate the neurodevelopmental processes associated with ASD. MRI “minor abnormalities” also included dilatation of the Virchow-Robin gaps, an enlarged cisterna magna, pineal gland cysts, and arachnid or choroidal cysts not included in specified categories. Methods